How to not know : the value of uncertainty in a world that demands answers - Stolzoff, Simone (W.W. Norton & Company, 2026)
"In the face of crushing uncertainty-whether in our careers, politics, or personal lives--it's natural to feel paralyzed and tempting to hide from the unknown or cling to false certainties. We try so hard to avoid the downsides of uncertainty that we miss out on its upside. Research shows that individuals, organizations, and communities with a high uncertainty tolerance tend to be more creative, innovative, adaptable, and resilient. Improving our ability to engage with uncertainty-managing the anxiety, stress, and fear of not being sure-opens us up to discovery. Through gripping stories of people grappling with big problems with no easy answers--from a college student trying to escape a religious cult to an economist trying to prevent the next financial crisis to residents of a Pacific island reckoning with the existential impact of climate change-acclaimed journalist and author of The Good Enough Job Simone Stolzoff offers practical advice on how to withstand the discomfort of ambiguity, admit what we don't know, and see the world in all its possibilities, instead of as we wish it to be. Blending engrossing storytelling, fascinating original research and reporting, and practical insights, How To Not Know invites readers to reframe uncertainty as a precursor to possibility and shares tools to face the unknown with courage and clarity"-- Provided by publisher.